Complexidade, melancolia, tabacaria - Fernandez, Maria Cristina Ribeiro (2020)
This dissertation undertakes the unreading of the poem The Tobacco Shop (1928) by Álvaro de Campos, heteronym of Fernando Pessoa, in the light - and in the shadow - of melancholy. The movement that the concept of melancholy goes through in history, from Ancient Greece to contemporary times, points out the intrinsic relationship between the melancholic state and art. The creation of the imaginary and the real as complementary spheres, simultaneous and inseparable, endow melancholy with mythic power and determine the dynamics of the poem by challenging Saturn – sovereign in its profound immanence, giant distant star, god of time and finitude – with the poetry. In the intertwining art-science, the objective of investigating the complexity of the melancholic state and the possibility of melancholy sublimation by artistic creation has in The Tobacco Shop the vastness to explore the human psyche with the reflections of social sciences and psychoanalysis